2018
DOI: 10.1016/j.jcct.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Low thigh muscle mass is associated with coronary artery stenosis among HIV-infected and HIV-uninfected men: The Multicenter AIDS Cohort Study (MACS)

Abstract: In this exploratory analysis, low thigh muscle mass was significantly associated with subclinical obstructive coronary stenosis. Additional studies involving larger sample sizes and prospective analyses are needed to confirm the potential utility of measuring mid-thigh muscle mass for identifying individuals at increased risk for obstructive CAD who might benefit from more aggressive risk factor management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The results of the present study should be interpreted by considering the minor differences between the included and excluded populations. Fourth, the sample of 475 patients was relatively large compared to that in previous studies of sarcopenia using CT in research on cardiovascular disease [11,12,13,14,15,16,17,28]. However, this sample size was not large enough to draw solid conclusions.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The results of the present study should be interpreted by considering the minor differences between the included and excluded populations. Fourth, the sample of 475 patients was relatively large compared to that in previous studies of sarcopenia using CT in research on cardiovascular disease [11,12,13,14,15,16,17,28]. However, this sample size was not large enough to draw solid conclusions.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies reported that sarcopenia assessed with various methods was closely associated with subclinical features of CAD, such as coronary artery calcification [8,27] and subclinical coronary artery stenosis [28]. However, the prognostic significance of sarcopenia in CAD based on real-world data has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of lean mass quantity and quality occurs with HIV infection, ART, and FHT [106,107] . Lean mass loss has been associated with mortality in the general population [108] , and lower lean mass is associated with greater subclinical obstructive coronary stenosis in men with and without HIV [109] . Thus, changes in lean and fat mass with HIV infection, ART, and FHT may converge to promote additive or synergistic immuno-metabolic and cardiometabolic disturbances in PLWH.…”
Section: Immuno-metabolic Effects Of Hivmentioning
confidence: 99%
“…Cumulative clinical evidence supports the relations between age-related loss of muscle mass and function, called sarcopenia, and insulin resistance, mitochondrial dysfunction, and systemic inflammation [ 6 , 7 ]. Specifically, decreased lower extremity appendicular skeletal muscle (LASM) is related to high risk for obstructive coronary heart disease [ 8 ]. One study reported that low LASM mass is associated with an increased ratio of hospitalization in patients with type 2 diabetes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%